Effect Of The Grounding System On The Lightning Current Profile Along A Tall Structure - Ir. Ts. Dr. Norhidayu Rameli; Mohd Zainal Abidin Ab-Kadir; Mahdi Izadi; Chandima Gomes; Norhafiz Azis (Institution of Engineering and Technology, 2024)
The behaviour of a lightning current traversing along a tall structure is influenced by the factor of the ground reflection coefficient parameter. This parameter is widely assumed to be constant in the analysis of lightning current along at all structure. However, in reality, the ground reflection depends on the relationship between the tower and ground impedances which results in multiple values for the ground reflection coefficient. These values are determined by the ground impedance, whereby the grounding electrode arrangement and soil resistivity play key roles. Hence, this study evaluates the effect of the grounding system on the lightning current profile along a tall structure. The lightning current along a tall structure is simulated by the implementation of a distributed source representation model. The results indicate that a multiple ground reflection coefficient is generated for different types of grounding electrode arrangements and soil resistivity values. The grounding electrode arrangement in horizontal, grid or circular forms provides at least a reduction of 30% reflected current along a tall structure for a high soil resistivity. Hence, this result may provide a general guide for telecommunication (TM) engineers to consider the condition of soil resistivity and the grounding system before installing a TM tower.